Além do 19 de Abril: A Lei 11.645/08 e o imaginário de estudantes da escola pública sobre os povos originários do Brasil - Queiroz, Pablo Wilson de (Universidade Federal de São Carlos, 2025)
The present work, of an investigative nature, had the purpose of contributing to the promotion of the debate on the context of Brazil's original population in public schools. The research aimed to understand, through critical reflection, the stereotypes and generalizations about the subject present during pedagogical interventions. Based on the experience of two meetings with a final-year high school class at E. E. Dr. Afonso Vergueiro, the goal was to construct the debate and praxis for future educational actions. The specific objectives aligned with the attempt to understand the effective practice of Law 11,645/08 in the school curriculum, problematize the results in the classroom, and include the valorization and recognition of indigenous culture in public schools.
Beyond April 19th: Law 11.645/08 and the collective imagination of public school students regarding the indigenous peoples of Brazil
Keywords: Geografia; Ensino; Povos originários; Geography; Education; Indigenous people; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável